2016
DOI: 10.1080/17453674.2016.1253329
|View full text |Cite
|
Sign up to set email alerts
|

Signs of knee osteoarthritis common in 620 patients undergoing arthroscopic surgery for meniscal tear

Abstract: Background and purpose — Recent evidence has questioned the effect of arthroscopic knee surgery for middle-aged and older patients with degenerative meniscal tears with or without concomitant radiographic knee osteoarthritis (OA). We investigated the prevalence of early or more established knee OA and patients’ characteristics in a cohort of patients undergoing arthroscopic surgery for a meniscal tear.Patients and methods — 641 patients assigned for arthroscopy on suspicion of meniscus tear were consecutively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 34 publications
2
24
0
2
Order By: Relevance
“…The majority of patients included in the development of the prognostic models were middle aged or older, reflecting current clinical practice 45–47. These patients typically have a degenerative meniscal tear,45 48 often in combination with other degenerative changes such as knee osteoarthritis (OA) 48 49. Symptoms are, therefore, likely to result from the multiple and complex processes of OA rather than the meniscal tear per se 50.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients included in the development of the prognostic models were middle aged or older, reflecting current clinical practice 45–47. These patients typically have a degenerative meniscal tear,45 48 often in combination with other degenerative changes such as knee osteoarthritis (OA) 48 49. Symptoms are, therefore, likely to result from the multiple and complex processes of OA rather than the meniscal tear per se 50.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Studies have reported improvements in pain, function, and quality of life after meniscal surgery with worse outcomes in patients of older age, with a greater body mass index, and with complex tears on arthroscopy. 4 As part of efforts to elucidate long-term outcomes, there has been increased focus on improving the accuracy and precision of patient-reported outcome measures (PROMs) while reducing question burden (the minimum number of responses necessary to produce a score on a given PROM instrument). 5 In 2004, the National Institutes of Health developed the Patient-Reported Outcomes Measurement Information System (PROMIS), a new outcome measure using item response theory and a large database of questions from various health domains.…”
mentioning
confidence: 99%
“…In this study, older patients mainly had degenerative meniscal tears and approximately half had severe cartilage defects (i.e., ICRS grade 3e4) in at least one compartment, indicative of early or more progressed stages of knee OA 1 . That suggests that in older patients other structures than the meniscal tear per se may be the cause of symptoms.…”
Section: Discussionmentioning
confidence: 82%
“…Patients with degenerative meniscal tears are considered a patient group with early signs of or at high risk of knee osteoarthritis (OA) 1,2 . Traumatic knee injury is also a well-established risk factor for later OA 3,4 , but data on patients under 40 years with meniscal tears constituting one such subgroup with traumatic knee injury is scarce.…”
Section: Introductionmentioning
confidence: 99%